Mutations in the leucine zipper of the human immunodeficiency virus type 1 transmembrane glycoprotein affect fusion and infectivity. - Dubay, J W (1992)
Many retroviruses, including the human and simian immunodeficiency viruses, contain a leucine zipper-like repeat in a highly conserved region of the external domain of the transmembrane (TM) glycoprotein. This region has been postulated to play a role in stabilizing the oligomeric form of these molecules. To determine what role this region might play in envelope structure and function, several mutations were engineered into the middle isoleucine of the leucine zipper-like repeat of the human immunodeficiency virus type 1 (HIV-1) TM protein. A phenotypic analysis of these mutants demonstrated that conservative mutations (Ile to Val or Leu) did not block the ability of the viral glycoprotein to mediate cell-cell fusion or affect virus infectivity. In contrast, each of the other mutations, except for the Ile-to-Ala change, completely inhibited the ability of the glycoprotein to fuse HeLa-T4 cells and of mutant virions to infect H9 cells. The alanine mutation produced an intermediate phenotype in which both cell fusion and infectivity were significantly reduced. Thus, the biological activity of the glycoprotein titrates with the hydrophobicity of the residue in this position. None of the mutations affected the synthesis, oligomer formation, transport, or processing of the HIV glycoprotein complex. Although these results do not rule out a role for the leucine zipper region in glycoprotein oligomerization, they clearly point to a critical role for it in a post-CD4 binding step in HIV membrane fusion and virus entry.